Intraperitoneal bilirubin administration decreases infarct area in a rat coronary ischemia/reperfusion model - Ben-Amotz, Ron; Bonagura, John; Velayutham, Murugesan; Hamlin, Robert; Burns, Patrick; Adin, Christopher A. (Frontiers in Physiology, 2014)
Bilirubin was previously considered a toxin byproduct of heme catabolism. However, a mounting body of evidence suggests that at physiological doses, bilirubin is a powerful antioxidant and anti-atherosclerotic agent. Recent clinical studies have shown that human beings with genetically-induced hyperbilirubinemia (Gilbert Syndrome) are protected against coronary heart disease. The purpose of this study was to investigate whether administration of exogenous bilirubin to normal rats would convey similar protective effects in an experimental model of coronary ischemia. We hypothesized that intraperitoneal bilirubin administration 1 hour before injury would decrease infarct area and preserve left ventricular (LV) systolic function when compared to non-treated rats. Coronary ischemia was induced by temporary (30 min) ligation of the left anterior descending coronary artery in control or bilirubin treated rats, followed by a 1-hour period of reperfusion. LV function was estimated by measurements of fractional shortening and fractional area shortening using echocardiography. LV function decreased in both experimental groups after ischemia and reperfusion, although in bilirubin-treated rats fractional shortening was less depressed during the period of ischemia (18.8 vs 25.8%, p = 0.034). Infarct size was significantly reduced in the bilirubin treated group compared to the non-treated group (13.34% vs 25.5%, p = 0.0067). Based on the results of this study, bilirubin supplementation appears to provide significant decrease in infarct size although protective effects on LV function were noted only during the period of ischemia. This result also suggests that lipid soluble antioxidant bilirubin prevents the oxidation of cardiolipin and decreases the infarct size in the heart during ischemia.